The Connection between Electronic Word-of-Mouth Communication, Destination Image, and Revisit Intention in Cruise Tourism - Avcı, Özkan; Sürücü, Çağrı (Journal of Tourism, Sustainability and Well-being, 2025)
Understanding tourists’ word-of-mouth communication, destination preferences, and revisit intentions is important in the rapidly growing cruise tourism industry. Focusing on Amasra, an emerging cruise destination on the Black Sea coast of Turkiye, this study examines the connection between electronic word-of-mouth (eWOM), destination image (DI) and tourists’ revisit intentions (RI). Structural equation modelling (SEM) analysis of data collected from 235 tourists. The analysis results proved that eWOM has an influence on DI and RI, DI has an influence on RI, and there is a mediating role between eWOM and RI. These findings highlight the potential for developing destinations such as Amasra to promote the natural beauty, old texture and ethnic richness of the region to a wider audience and to create long-term loyalty by strengthening tourists’ emotional attachment to the destination. The research highlights the role of relevant factors in the sustainable success of cruise destinations. Focusing on these factors can increase tourists’ intention to revisit the destination through strategic marketing, public relations, and destination management efforts. This can support both economic gains and the long-term competitiveness of the destination.